Differences in Fracture Healing Between Female and Male C57BL/6J Mice - Haffner-Luntzer, Melanie; Fischer, Verena; Ignatius, Anita (Frontiers in Physiology, 2021)
Background: Mice are increasingly used in fracture healing research because of the opportunity to use transgenic animals. While both, male and female mice are employed, there is no consensus in the literature whether fracture healing differs between both sexes. Therefore, the aim of the present study was to analyse diaphyseal fracture healing in female and male C57BL/6J mice, a commonly used mouse strain in bone research. Methods: For that purpose, 12-week-old female (17–20 g) and male mice (22–26 g) received a standardised femur midshaft osteotomy stabilised by an external fixator. Mice were euthanized 10 and 21 days after fracture and bone healing was analysed by biomechanical testing, µCT, histology, immunohistochemistry and qPCR. Results: Ten days after fracture, male mice displayed significantly more cartilage but less fibrous tissue in the fracture callus compared to female mice, whereas the amount of bone did not differ. At day 21, male mice showed a significantly larger fracture callus compared to female mice. The relative amount of bone in the fracture callus did not significantly differ between both sexes, whereas its tissue mineral density was significantly higher in male mice on day 21, indicating more mature bone and slightly more rapid fracture healing. These results were confirmed by a significantly greater absolute bending stiffness of the fractured femurs of male mice on day 21. On the molecular level, male mice displayed increased active β-catenin expression in the fracture callus, whereas oestrogen receptor α (ERα) expression was lower. Conclusions: These results suggest that male mice display more rapid fracture healing with more prominent cartilaginous callus formation. This might be due to the higher weight of male mice, resulting in increased mechanical loading of the fracture. Furthermore, male mice displayed significantly greater activation of osteoanabolic Wnt/β-catenin signalling, which might also contribute to more rapid bone regeneration.